Late Holocene Glacial History of Sólheimajökull, Southern Iceland - Bjarki Friis 1974- (2011)
Sólheimajökull is an outlet glacier draining the Mýrdalsjökull ice cap in southern Iceland. Mýrdalsjökull covers the Katla central volcano, one of the most active volcanoes in Iceland. Sólheimajökull is ~ 15 km long, 1-2 km wide and covers 44 km². It descends from the Katla caldera at 1505 m a.s.l. (Hábunga), and terminates ~ 100 m a.s.l. The base of the glacier is at 11 m above present sea-level, 0.8 km inside the present margin. Subglacial eruptions of Katla have caused jökulhlaups at Sólheimajökull, with great impact on the proglacial landscape. The marginal fluctuations of Sólheimajökull correspond well to changes in the climate. In 2010, the glacier had retreated 1255 meter since annual ice front measurements were initiated in 1931, however, punctuated by a period of advance from 1969-1995. The objectives of this study are firstly to: (i) map and interpret landforms and sediments exposed in the forefield since 1995: (ii) map and interpret changes in the size and extent of the glacier during the Little Ice Age (14th – 19th century AD): (iii) confine the extent of the glacier during the Late Holocene. This has been done by analyzing a series of aerial photographs from 1945 to present using a topographical map from 1904 for reference. Fieldwork conducted during the summer of 2009 offered the possibility to check the quality of the remote sensing as well as to do stratigraphical and sedimentological work in the glacier forefield. Radiocarbon dates confine the end moraines in front of Sólheimajökull to the period after AD 1445 +/- 45, which is important for reconstructing the extent of the Little Ice Age glacial advances. Furthermore, geomorphological mapping shows a number of recently exposed landforms that allow reconstruction of the processes operating during these advances and subsequent retreats. Dates derived from cosmogenic exposure dating show that the eastern flank of Sólheimajökull reached the outer-most moraine at AD 56, whereafter it retreated to the penultimate moraine at AD 91. Mt. Jökulhaus has ...